Atorvastatin reduces cardiac and adipose tissue inflammation in rats with metabolic syndrome. (1st August 2017) - Yamada, Yuichiro; Takeuchi, Shino; Yoneda, Mamoru; Ito, Shogo; Sano, Yusuke; Nagasawa, Kai; Matsuura, Natsumi; Uchinaka, Ayako; Murohara, Toyoaki; Nagata, Kohzo
Abstract: Background: Statins are strong inhibitors of cholesterol biosynthesis and help to prevent cardiovascular disease. They also exert additional pleiotropic effects that include an anti-inflammatory action and are independent of cholesterol, but the molecular mechanisms underlying these additional effects have remained unclear. We have now examined the effects of atorvastatin on cardiac and adipose tissue inflammation in DahlS. Z - Lepr fa /Lepr fa (DS/obese) rats, which we previously established as a model of metabolic syndrome (MetS). Methods and results: DS/obese rats were treated with atorvastatin (6 or 20 mg kg − 1 day − 1 ) from 9 to 13 weeks of age. Atorvastatin ameliorated cardiac fibrosis, diastolic dysfunction, oxidative stress, and inflammation as well as adipose tissue inflammation in these animals at both doses. The high dose of atorvastatin reduced adipocyte hypertrophy to a greater extent than did the low dose. Atorvastatin inhibited the up-regulation of peroxisome proliferator–activated receptor γ gene expression in adipose tissue as well as decreased the serum adiponectin concentration in DS/obese rats. It also activated AMP-activated protein kinase (AMPK) as well as inactivated nuclear factor–κB (NF-κB) in the heart of these animals. The down-regulation of AMPK and NF-κB activities in adipose tissue of DS/obese rats was attenuated and further enhanced, respectively, by atorvastatin treatment. Conclusions: The present results suggest that the anti-inflammatory effects of atorvastatin on the heart and adipose tissue are attributable at least partly to increased AMPK activity and decreased NF-κB activity in this rat model of MetS. Highlights: We investigate the effects of atorvastatin on cardiac and adipose tissue pathology and metabolism in rats with MetS. Atorvastatin reduces cardiac fibrosis, diastolic dysfunction, oxidative stress and inflammation. Atorvastatin ameliorates adipocyte hypertrophy and inflammation in visceral adipose tissue. Atorvastatin alleviates insulin resistance and glucose intolerance despite a decrease in circulating adiponectin levels. The effects of atorvastatin are attributable at least partly to increased AMPK activity and decreased NF-kB signaling.